PENGEMBANGAN JABATAN FUNGSIONAL DI LINGKUNGAN PEMERINTAH DAERAH - Ambar Teguh Sulistiyani (Jurnal Manajemen Kepegawaian, 2007)
Recently, beaurocratic reformation creates a new political condition for many aspects in governmental development. Especially, public services and political participation increase in the autonomy. Government has agenda to implement compulsory affairs independenly. Government has a program to increase good public services of civil servants. Functional career as part of civil servants is necessary to improve personnel’s capacity with functional career development. There are four aspects to develop functional career. The aspects are legalistic, technical, economic and public needs. Kata kunci: Pengembangan, jabatan fungsional, karir fungsional A.